2012
DOI: 10.4161/auto.18777
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput FRET-based assay for determination of Atg4 activity

Abstract: Atg4 is required for cleaving Atg8, allowing it to be conjugated to phosphatidylethanolamine on phagophore membranes, a key step in autophagosome biogenesis. Deconjugation of Atg8 from autophagosomal membranes could be also a regulatory step in controlling autophagy. Therefore, the activity of Atg4 is important for autophagy and could be a target for therapeutic intervention. In this study, a sensitive and specific method to measure the activity of two Atg4 homologs in mammalian cells, Atg4A and Atg4B, was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 32 publications
1
86
1
Order By: Relevance
“…Therefore, the BRET-based assay could be used to monitor the rate of autophagy in leaf tissue during a specific biological process. Recently, fluorescence resonance energy transfer (FRET)-based human Atg8 substrates have been described for quantitative measurement of hAtg4 activity in vitro and in mammalian cell lysates (22). Although the FRET-based assay is highly sensitive, the direct excitation of the acceptor fluorophore by the external light for activation of the donor fluorophore influences successful FRET (23).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the BRET-based assay could be used to monitor the rate of autophagy in leaf tissue during a specific biological process. Recently, fluorescence resonance energy transfer (FRET)-based human Atg8 substrates have been described for quantitative measurement of hAtg4 activity in vitro and in mammalian cell lysates (22). Although the FRET-based assay is highly sensitive, the direct excitation of the acceptor fluorophore by the external light for activation of the donor fluorophore influences successful FRET (23).…”
Section: Discussionmentioning
confidence: 99%
“…120 It is also possible to use assays with an artificial fluorogenic substrate, or a fusion of LC3B to phospholipase A(2) that allows the release of the active phospholipase for a subsequent fluorogenic assay, 121 and there is a FRETbased assay utilizing CFP and YFP tagged versions of LC3B and GABARAPL2 that can be used for high-throughput screening. 122 Another method to monitor ATG4 activity in vivo uses the release of Gaussia luciferase from the C terminus of LC3 that is tethered to actin. 123 Note that there are four Atg4 homologs in mammals, and they have different activities with regard to the Atg8 subfamilies of proteins.…”
mentioning
confidence: 99%
“…A very recent publication has given strong direct evidence for the potential of inhibitors of ATG4B in treating cancer. Atkin et al 27 identified a small molecule ATG4B inhibitor with moderate potency (IC 50 51 lM as tested in an assay developed by Li et al) 28 from in silico docking of small molecules from the NCI library into the ATG4B active site. In spite of its rather low potency, the authors showed that the compound, NSC185058, suppressed formation of autophagic vesicles in starved cells, suppressed activation and lipidation of LC3 and, most significantly, suppressed autophagic markers in livers of fasted mice, and suppressed autophagy and growth of osteosarcoma tumors both in vitro and in vivo in immunodeficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…During the past several years we, 29 and others, 28,[30][31][32] have developed a number of protocols for assaying small molecule ATG4B inhibitors. We previously developed an assay based on the cleavage of pro-LC3 followed by mass spectrometry (LC-MS assay).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation